Infection-relapse and a potentially surgical stratification model for the treatment of mycotic aortic aneurysms: A propensity-matched pilot study. (October 2019) - Liu, Mingyuan; Liu, Peng; Liu, Bin; Che, Haijie; Liu, Junjun; Sun, Anqiang; Li, Wei; Zhang, Xiaoming; ,
Objective: This study evaluates the overall survival and the infection-relapse after endovascular repair (Endo) vs. open surgery (Open) for mycotic aortic aneurysms and the potential influence of perioperative severity of infection to the decision-making on the long-term survival. Design: A multicenter, retrospective analysis of 5247 consecutive aortic aneurysm repair performed from January 2003 to December 2017 at five tertiary medical centers was conducted. Among the study population, 257 patients with mycotic aortic aneurysms s were identified. Methods: Finally, 73 patients were enrolled in the cohort after exclusion and a 1:1 propensity-matched analysis. The study cohort drawn from matched data included 37 patients in the Endo group and 36 patients in the Open group. The primary endpoint was overall survival. Secondary endpoints included infection-relapse during the follow-up. Univariate and multivariate Cox regression analyses were used to assess predictors for late mortality. Results: The mean follow-up time for the entire cohort was 41 months (range, 1 to 135 months). Among propensity-matched patients, there was no significant difference in baseline characteristics. There was no difference in overall survival ( P  = 0.083) between the groups at five years, but Open group was associated with a lower infection-relapse incidence during the follow-up ( P  = 0.011). Subgroup analysis revealed a better survival rate for Open in patients with severe infection ( P  = 0.003) or small periaortic abscess ( P  = 0.049). Conclusion: There were no significant differences between Endo and Open in overall survival. However, Open was a more definite option with less infection-relapse and had potential advantages for patients with severe infection or with a small periaortic abscess.